Analysis of Distribution and Marketing Margin of Topo Local Shallots in North Tidore District, Tidore Islands City - Munawir Muhammad; Fatmawati Fatmawati; Abdul Haris Din (Sangia Publishing, 2020)
The purpose of this research was to analyze the form of topo local shallot marketing distribution channels and marketing margins of topo local shallots in North Tidore District, Tidore Islands City. Respondents which will be researched include producers, collectors, retailers and consumers who are directly involved in the distribution of topo local shallots. The data collection techniques used in this research included farmers, collector traders, retailers involved in developing topo local shallot commodities in North Tidore District, Tidore Islands City, by filling out a questionnaire followed by interviews. The data analysis used consisted of descriptive analysis and quantitative analysis (marketing margin analysis). Through the research results that the marketing channels carried out by local shallot farmers Topo in North Tidore District have 3 marketing distribution channels (1) Farmer-Trader, Collector-Trader, Retailer and consumer. (2) Farmers, Retailers and Consumers. (3) Farmers directly to the final consumer. The marketing margin in channel I is Rp. 17,500 and channel II is Rp. 10,000. The highest margin is obtained in the marketing channel I, they are farmer-trader-gatherer-retailer-consumer, so that causes part received by farmers is less than the traders. Channel III has no margin because the farmers sell their products directly to consumers. So that the most profitable channel for producers is the marketing channel III.